Evaluation of the quality of life and the incidence of stress urinaryincontinence in nulliparous women training selected sports:a cross-sectional survey pilot study - Tarczewska, Anna; Kołodyńska, Gabriela; Zalewski, Maciej; Mucha, Anna; Piątek, Aleksandra; Andrzejewski, Waldemar (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. The number of women suffering from urinary incontinence is increasing every year. The most common type of thiscondition is stress urinary incontinence. Involuntary leakage of urine occurs when sneezing, coughing, laughing, and standingup, as well as during physical activity. The problem of urinary incontinence is very embarrassing for athletes and affects theirsports performance. The aim of the study was to assess the occurrence of urinary incontinence symptoms in women regularlytraining in selected sports.Methods. 64 women athletes were selected for the study. This pilot study involved women training in athletics (short-distancerunning, long-distance running, hurdles and jumping (high jump, long jump, triple jump, pole vault), basketball, volleyball, orstrength sports). Women were selected based on sample size calculation from those training in specified clubs. Women whohad given birth were excluded from the study. The subjects completed a proprietary questionnaire consisting of 8 questions.They also completed the Urinary Distress Inventory, Short Form (UDI-6SF) questionnaire and the Incontinence Impact Questionnaire, Short Form (IIQ-7).Results. In this study, 43% of women who trained had symptoms of urinary incontinence. Regression analysis results withUDI-6SF and IIQ-7 total scores as dependent variables and age as an independent variable showed that the slopes of regressionwere not statistically significantly different (p-value > 0.05). The results of the analysis of the correlation between SUI (stressurinary incontinence) and age (p = 0.0247) and practiced sport (p = 0.0476) turned out to be statistically significant.Conclusions. The type of sport practiced affects the occurrence of UI (urinary incontinence) symptoms in women. In this study,female athletes practicing strength sports had the greatest predisposition to the occurrence of UI symptoms. The occurrenceof UI symptoms has little impact on the deterioration of the quality of life among women practicing selected sports.
Keywords: stress urinary incontinence (SUI); quality of life; training selected sports